2019
DOI: 10.1177/1559325819837795
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Circular RNA Expression Profile in HEK 293T Cells Exposed to Ionizing Radiation

Abstract: Radiation therapy is one of the most common cancer treatments. It is important to understand how cells respond to ionizing radiation (IR) to improve therapeutic efficacy. Circular RNAs (circRNAs) recently have been found to regulate a variety of cellular processes. However, it is poorly defined that their expression pattern and their identity in cells following IR exposure. Here, we performed high-throughput sequencing and comprehensive analysis of circRNA expression in human embryonic kidney (HEK) 293T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…This cell line is a variant of the HEK 293 lineage, which was isolated from kidney epithelial cells extracted from human embryos ( 49 ). Both lines are widely used in research due to their high transfectability, gene expression, and production of proteins or recombinant retrovirus ( 23 , 49 , 50 ). The HEK 293T variant expresses the T SV-40 antigen, which enables the amplification of transfected plasmids containing the SV40 origin of replication and thus considerably increases the expression levels of desired gene products ( 50 ).…”
Section: In Vitro Models ( Table 1 )mentioning
confidence: 99%
See 1 more Smart Citation
“…This cell line is a variant of the HEK 293 lineage, which was isolated from kidney epithelial cells extracted from human embryos ( 49 ). Both lines are widely used in research due to their high transfectability, gene expression, and production of proteins or recombinant retrovirus ( 23 , 49 , 50 ). The HEK 293T variant expresses the T SV-40 antigen, which enables the amplification of transfected plasmids containing the SV40 origin of replication and thus considerably increases the expression levels of desired gene products ( 50 ).…”
Section: In Vitro Models ( Table 1 )mentioning
confidence: 99%
“…Both lines are widely used in research due to their high transfectability, gene expression, and production of proteins or recombinant retrovirus ( 23 , 49 , 50 ). The HEK 293T variant expresses the T SV-40 antigen, which enables the amplification of transfected plasmids containing the SV40 origin of replication and thus considerably increases the expression levels of desired gene products ( 50 ). These cells have also previously been used in studies of other such viruses as herpes simplex virus, SARS-CoV, and even CoV pseudovirions ( 34 , 51 53 ).…”
Section: In Vitro Models ( Table 1 )mentioning
confidence: 99%
“…In GBM, circ-AKT3 is reported to encode AKT3-174aa, a novel tumor suppressor protein, and enhance radiation sensitivity cells by negatively regulating the PI3K/Akt pathway [207]. Besides, high-throughput sequencing and bioinformatic analysis reveals significant circRNAs expression in cancer radioresistance, like hsa_circ_0004015 [208], circRNA_001059 and circRNA_000167 [209] circATP8B4 [210], hsa_circ_0000734 [211], etc., which establishes the circRNA-miRNA-target gene interaction network. One circRNA can target various miRNAs, and one miRNA can also suppress its downstream genes.…”
Section: Circrnas In Cancer Radioresistancementioning
confidence: 99%
“…CircATP8B4 is one of the circRNAs in extracellular vesicles isolated from radioresistant glioma cells and induces therapy resistance by sponging U251 miR-766 [210]. Hsa_circ_0000734 is discovered to modulate hsa-miR-432-5p and hsa-miR-124-5p, which can further control the expression of target genes [211]. As a result, circRNAs play a comprehensive role in tumor radiotherapy, which provides some new insights on therapeutic approaches.…”
Section: Circrnas In Cancer Radioresistancementioning
confidence: 99%
“…It was identified that 61 circRNAs are upregulated and 97 are downregulated in human embryonic kidney (HEK) 293 T cells following radiation. The circRNA-miRNA-mRNA network analysis revealed that the altered circRNAs were suggested to be involved in EGFR and mTOR signaling, which is worth further studies in cancer cells [154]. Duo et al identified 76 upregulated and 77 downregulated circRNAs in irradiated HeLa cells.…”
Section: Miscellaneousmentioning
confidence: 99%